2006
DOI: 10.1177/036215370603600304
|View full text |Cite
|
Sign up to set email alerts
|

Impasse and Intimacy: Applying Berne's Concept of Script Protocol

Abstract: The concept of impasse was first conceptualized in the transactional literature as an intrapsychic process that inhibited or blocked internal communication among states of the ego. The authors present an understanding of impasse as an interpersonal process that disrupts the work of the professional dyad in promoting self-understanding and development. As the working relationship deepens, it develops an unavoidable intimacy or closeness, with many of the same pleasures and problems that attend any close relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 19 publications
0
55
0
Order By: Relevance
“…This is mirrored in the research on effective and ineffective supervision done by Landany, Mori, and Mehr (2013), who found that the quantifiable variables under examination-such as supervisory working alliance, supervisor style, and supervisor (non)disclosure-were inextricably linked with and influenced the outcomes for both the therapy and the supervision process. Transference and countertransference (emotional reactions), along with interpretations by therapists and supervisors, can show how feelings, behavior, and expressions toward them are based on parallel processes (Cassoni, 2007;Clarkson, 1991;Cornell & Landaiche, 2006). The research of Safran, Muran, Samstag, and Winston (2005) found that when a poor therapeutic alliance during the therapy process is taken to supervision, a more collaborative examination there resulted in less blaming of the client.…”
Section: Review Of the Supervision Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This is mirrored in the research on effective and ineffective supervision done by Landany, Mori, and Mehr (2013), who found that the quantifiable variables under examination-such as supervisory working alliance, supervisor style, and supervisor (non)disclosure-were inextricably linked with and influenced the outcomes for both the therapy and the supervision process. Transference and countertransference (emotional reactions), along with interpretations by therapists and supervisors, can show how feelings, behavior, and expressions toward them are based on parallel processes (Cassoni, 2007;Clarkson, 1991;Cornell & Landaiche, 2006). The research of Safran, Muran, Samstag, and Winston (2005) found that when a poor therapeutic alliance during the therapy process is taken to supervision, a more collaborative examination there resulted in less blaming of the client.…”
Section: Review Of the Supervision Literaturementioning
confidence: 99%
“…Autoethnography provides a methodology (buttressed by its own critical literature, for example Pennington & Prater, 2016;Siddique, 2011) for including the inner life of the supervisor-considered as both subject and object of the study-as evidence. Ideas of transference and countertransference (emotional reactions), along with interpretations by the therapists and supervisors, provide a framework for exploring the feelings, behaviors, and expressions that arise in parallel between supervisor and supervisee (Cassoni, 2007;Clarkson, 1994;Cornell & Landaiche, 2006). I see the relational and reciprocal potential of two or more individuals encountering a co-created space in which supervision takes place.…”
Section: Examples From My Experience As a Supervisee And Supervisormentioning
confidence: 99%
“…He considered this kind of stereotype plate to have been created by each individual "through the combined operation of his innate disposition and the influences brought to bear on him during his early years" (p. 99). This is very similar to Berne's (1963) concept of protocol, a term he used to denote a crude pattern or template created unconsciously from early experiences of significant others, a template that is then later used to form the individual's life script (see Cornell & Landaiche, 2006;Steele, 1985). In other words, current interpersonal interactions appear to be complicated at times by the emergence of unconscious patterns of relating that seem to be more deeply imprinted than script and that operate in a compelling, automatic way.…”
Section: The Relevance Of Transference For Transactional Analysismentioning
confidence: 79%
“…Tom realized that his defensiveness and rebellion were similar to how he acted toward his older brother, who was often critical of him. Cornell and Landaiche (2006) described transference and countertransference as unconscious communications and interpersonal processes from the client to the therapist arising from the client's emotional (Child ego state) confusion of the therapist with an early parental figure that causes the therapist to seem to the client to feel and behave like the historical figure. Berne's game theory provides one avenue for analyzing and intervening in the interpersonal communication patterns that sustain transference/ countertransference dynamics.…”
Section: Case Examplesmentioning
confidence: 99%